Strategic Planning of Information System and Information Technology in Small and Medium Enterprises with Reference to PT. Giri Artha Sejahrera - Burhanudin Burhanudin; Sani Muhamad Isa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
From the authors’ initial interviews with the top managers of some small and medium enterprises (SMEs), it was found that the high cost of implementing and maintaining information technology (IT) and information system (IS) was one of obstacles they faced. SMEs that want to use IT for their business processes need to spend some money on the implementation and maintenance of and investment in IT, which is considered too expensive for many of them. The main objective of this study is to examine the adoption of IS and IT strategic planning in SMEs. To meet this objective, a car driving school company, i.e. PT. GAS, was selected as the subject of this study. As a qualitative-based study, it used a descriptive method of analysis with a number of analyses conducted in stages based on a strategic planning framework in IS and IT in accordance with the Ward and Peppard framework. Based on the results, this study concludes that PT GAS could implement IS and IT strategic planning at a low cost by contracting a web-based information system developer with per-user payments.